SISTEM PEMILIHAN LAPTOP TERBAIK DENGAN MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Susliansyah Susliansyah; Ririn Restu Aria; Susi Susilowati (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
The Weighted Product method requires a normalization process because this method assumes the results of evaluating each attribute. The results of these multiplications have not been meaningful if they have not been compared (divided) with standard values. The weight for the benefit attribute functions as a positive power in the multiplication process, while the weight of the cost functions as a negative rank. The Weighted Product method uses multiplication as a linking attribute rating, where the rating of each attribute must be raised first with the corresponding weight. Weighting Product Weighted method is calculated based on the level of importance. This system requires input weight values based on prospective buyers' needs in the form of prices, RAM capacity, processor type, Harddisk capacity, and VGA (Video Graphics Array). The results of this study provide laptop recommendations according to specification requirements for prospective buyers with 100% calculation accuracy based on manual calculations and calculations on laptop selection decision support systems.